Targeted Blood Brain Barrier Opening With Focused Ultrasound Induces Focal Macrophage/Microglial Activation in Experimental Autoimmune Encephalomyelitis - Schregel, Katharina; Baufeld, Caroline; Palotai, Miklos; Meroni, Roberta; Fiorina, Paolo; Wuerfel, Jens; Sinkus, Ralph; Zhang, Yong-Zhi; McDannold, Nathan; White, P. Jason; Guttmann, Charles R. G. (Frontiers in Neuroscience, 2021)
Experimental autoimmune encephalomyelitis (EAE) is a model of multiple sclerosis (MS). Focal lesions are less frequent in EAE, and can neither be constrained to specific locations nor timed to occur at a pre-specified moment. We sought to develop a controlled model of inflammatory, focal brain lesions in EAE using focused ultrasound (FUS). Lesion development was monitored with magnetic resonance imaging (MRI) and magnetic resonance elastography (MRE) and analyzed by histopathology. EAE was induced in 12 6-8 weeks old female C57BL/6 mice. FUS-induced blood brain barrier disruption (BBBD) was performed 6, 7 and 9 days after immunization in subgroups of four animals and in a control group. MRI and MRE were performed on a 7T small animal MRI scanner 2 and 3 weeks after immunization and 1 week after sonication in controls. Contrast-enhanced T1-weighted and T2-weighted sequences and MRE with a vibration frequency of 1 kHz were acquired. Animals were then sacrificed for histopathology. T2-weighted hyperintensities and foci of activated microglia/macrophages were observed in the sonicated hemisphere of a subset of animals with EAE, but were absent in not immunized control animals. Larger cellular infiltrates or apparent demyelination were not identifiable. EAE-animals tended to have lower viscoelasticity and elasticity in the sonicated parenchyma. This trend was significant when comparing the sonicated to the normal hemisphere and specifically the sonicated compared to the normal cortex in animals sonicated nine days after immunization (sonicated vs. normal hemisphere: mean viscoelasticity 6.1 kPa vs. 7.2 kPa; p = 0.003, mean elasticity 4.9 kPa vs. 5.7 kPa, p = 0.024; sonicated vs. normal cortex: mean viscoelasticity 5.8 kPa vs. 7.5 kPa; p = 0.004, mean elasticity 5.0 kPa vs. 6.5 kPa; p = 0.008). Control animals showed no differences between sonicated and contralateral parenchyma. We here provide first evidence for a controlled lesion induction model in EAE using FUS-induced BBBD. The observed lesions in EAE are consistent with foci of activated microglia that may be interpreted as targeted initial inflammatory activity, and which have been described as pre-active lesions in MS. Such foci can be identified and monitored with MRI and seem to influence biomechanics.